PENGARUH PENGGUNAAN MEDIA INTERAKTIF VIDEO KINEMASTER TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK TERPADU KELAS IV SDN GUGUS 1 KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - Widiya, Widiya; Reinita, Reinita (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This study inspires researchers to use learning media that are not yet creative in carrying out learning. With the aim of knowing how the effect of using kinemaster video interactive media on student learning outcomes in integrated thematic learning for class IV SDN Gugus 1, Junjung Sirih District, Solok Regency. This study uses quantitative research methods in a manner similar to experiments. Using an unbalanced control group design. The data collection method used random sampling, all fourth grade students of SDN Gugus 1, Junjung sirih sub-district, Solok district were used as the sample population in this study, which was chosen as the sample was grade IV SD IT Dambaan Ummah as an experimental class and grade IV SDN 10 Paninggahan as a class. control with the number of students in each class 15 people. The instrument of this research is an objective test with multiple choice type. According to the researchers' findings, the average value of the experimental class was 81.53 standard deviations, or 8.05. while the average value for the control class was 18.95 or a standard deviation of 63.4. Based on the t-test calculation, tcount is 3.22 while ttable is 2.048 at a confidence level of 0.05, meaning that tcount is greater than ttable. The use of Kinemaster video interactive media on student learning outcomes in class IV integrated theme learning at SDN Gugus 1, Junjung Sirih District, Solok Regency can be concluded to have a beneficial and substantial impact.